Modelagem de nicho, variabilidade genética e conservação de Anomochloa maranteidea Brongn (Poaceae) endêmica do sul da Bahia, Brasil - Vieira, João Paulo Silva (2017)
The genus Anomochloa Brongn. includes a single species, A. marantoidea Brongn., known as the earliest extant grass. It is a rare species from the Brazilian Atlantic rainforest, endemic to the southern Bahia. Only two populations were discovered so far, occurring out protected areas with few individuals registered, thus, A. marantoidea is considered critically threatened with extinction. The study of this species is highly important to understand evolutionary processes within Poaceae family. The present study aimed to increase the knowledge about its geographic range, to evaluate its potential areas of occurrence and to access its genetic diversity, detecting probable genetic threats as a result of its small population size. These data are essential for the development of conservation programs. Two new populations were recently discovered and the modeled ecological niche to A. marantoidea did not diverge from the expected geographical extent, denoting high climatic restriction and reasserting its rarity. The variables Index of Tree Cover and Rainfall are the main components that influence its restricted distribution. The levels of genetic diversity within the populations accessed by molecular markers indicate that A. marantoidea exhibits capacity for favorable response in short time and a conservation plan may be efficient to maintain its current genetic diversity. This diversity is correlated to the population size, for this reason, the propagules necessary for establishing new populations in climatically suitable sites must be originated from the largest populations. Genetic structure analysis suggests recent fragmentation and low gene flow among populations showing high levels of inbreeding. In this way, we recommend human mediated gene flow between the populations in order to mitigate the risks of inbreeding depression. It is hypothesized that the genetic differences among populations are caused mostly by random drift, resulting in populations with few individuals more genetically differentiated than the large ones. This implies that a minimum number of individuals (~100) is desirable to avoid the decrease of genetic diversity in populations.